BRUCELLAR SPONDYLITIS MIMICKING LUMBAR DISC HERNIATION - CASE-REPORT - (:unkn) unknown (STOCKTON PRESS, 1995)
In this paper, a patient with brucellar spondylitis who was initially diagnosed as having a lumbar disc herniation is presented. As the disc tissue enlarges in the early stages of discitis because of the inflammatory reaction, it may compress the related root(s) mimicking a disc herniation. For this reason infectious discitis, as in our case, should be kept in mind in the differential diagnosis of the radicular symptoms caused by a disc herniation. The crucial role of magnetic resonance imaging in making the differential diagnosis of the case is especially emphasized.
Keywords: BRUCELLOSIS; SPONDYLITIS; LUMBAR DISC HERNIATION; MRI STUDY